Single leg pedaling exercises and their effect on experienced cyclists pedaling technique - Gervais, P.; Ellis, D. G. (2002)
A significant (P=.007) difference between pre-test (60.5%) and post-test (62.8%) pedal stroke efficiency was observed (as measured by average pedal cycle power output/peak pedal stroke power output)(see Table 1) but no change in metabolic efficiency was observed. There was no increase in power output at ventilatory threshold and VO2max after the training period. Absolute VO2max and TT time were however improved (p<0.05) Oxygen consumption and metabolic efficiency during the TT predicted race time both before